RISK MANAGEMENT IMPLEMENTATION FOR GAS PRODUCTION PROJECT AT KSO PERTAMINA EP - TECHWIN BENAKAT TIMUR - HARYANTO PURWADI (NIM 29114597), RIO
PT. KSO Pertamina EP – Techwin Benakat Timur is subsidiary of PT. Techwin Energy, was established on May 2012, which the main business is oil & gas production. Benakat Timur an onshore field located in South Sumatra. Geographically, BenakatTimur field is located 15 km west of Palembang, or 60 km from Prabumulih; it can also be reached from Pendopo ± 8 km to the east. By February 2014, a total of 61 wells were drilled at Benakat Timur field where there were 23 producing wells, 10 dry wells, 3 injection wells and 25 others suspended wells. Most of the wells were vertical wells except for wells 55, 57 and BRN-02 which are deviated wells. Artificial lift methods used for producing oil and gas from layer A to layer N consisted of two types, Namely Pumping units and ESP. Because of the current low oil price situation KSO Pertamina EP – Techwin Benakat Timur plan to develop or start to produce gas in the Bernai Block and Bulu Block in the benakat Timur field. This is very crucial to KSO Pertamina EP – Techwin Benakat Timur because it is the most economical way to increase prodution (BOE/day) and it can help KSO Pertamina EP –Techwin Benakat Timur to claim unrecovered cost a lot faster.